The Effect Of Thin Capitalization, Accounting Conservatism, Sales Growth And Transfer Pricing On Tax Avoidance - Wandro Mahendra; Ginanjar Adi Nugraha; Sully Kemala Octisari (IAEI, 2023)
This research aims to determine and analyze the influence of thin capitalization, accounting conservatism, sales growth, and transfer pricing on tax avoidance in energy companies listed on the Indonesia Stock Exchange in 2019-2022. The research method used is a quantitative method. The data in this research is secondary data in the form of financial reports of Energy companies listed on the Indonesia Stock Exchange for 2019-2022. The population of this research was 36 companies and the total research sample was 16 companies. The sampling technique used was purposive sampling. Data analysis used was panel data regression. The test results for each variable show that thin capitalization and sales growth have an insignificant positive effect on tax avoidance, while accounting conservatism and transfer pricing have an insignificant negative effect on tax avoidance.